Development of Suspended Particulate Matter Empirical Equation for Tropics Estuary from Landsat ETM+ Data - Z Razak; A Zuhairi; S Shahbudin; Y Rosnan (ASEAN Journal on Science and Technology for Development, 2014)
Suspended Particulate Matter (SPM) essentially related to the total scattering of particles in the water column. It plays the role as a transport medium for pollutants, total load of organic and inorganic substance in the water phase. In this study, we have developed empirical relationship based on a strong relationship between Landsat near infrared (NIR) band and archived SPM data. The following were the power equations:SPM NE (mg/l) = 11.68x0.666SPM SW (mg/l) = 18.61x0.493where, x (TM4) is radiance of ETM+ NIR band 4 was developed under tropical atmospheric conditions. Using the above equation, the SPM concentration for Northeast and Southwest monsoon in the Pahang River estuary as a case study was determined. The mean SPM concentration and mean reflectance value during Northeast monsoon were 131.69 mg/l and 0.135 mg/l. The mean SPMconcentration value and reflectance were 95.94 mg/l and 0.078 mg/l during the Southwest monsoon. Generally, from remote sensing archive data and above equations, the SPM concentrations of Pahang River were successfully determined from 1999 to 2012.